Time as a Category in Survivors’ Reports About Child Sexual Abuse: An Explorative Approach to Lifetime Abuse - Andresen, Sabine (Journal of interpersonal violence, 2024)
Since the 1990s, cases of serious violence and abuse, particularly sexual abuse in educational and social institutions of the Catholic Church, have been reported in numerous countries, including Ireland, the United States, and Australia. In many countries, commissions have been set up to investigate the widespread cases of abuse that could not be prosecuted under criminal law. The testimonies of survivors and other witnesses are used by the commissions of inquiry in their work. Since 2016 the Independent Inquiry into Child Sexual Abuse in Germany has collected more than 2,500 reports from survivors of child sexual abuse. Forty-four testimonies were analyzed in a study seeking to understand more about lifetime abuse. In an explorative analysis, aspects of time as a key category in the reports were identified using the structured content analysis method. The results highlight the importance of time in the reports and during all phases of the survivors’ lives. Overall, four themes are relevant: (a) the identification of turning points, (b) time to make sense of what happened, (c) the practice of waiting, and (d) time-bound experiences of testifying.